2022
DOI: 10.3389/fcvm.2022.922616
|View full text |Cite
|
Sign up to set email alerts
|

Sub-satisfactory recanalization of severe middle cerebral artery stenoses can significantly improve hemodynamics

Abstract: PurposeTo investigate the effect of sub-satisfactory stent recanalization on hemodynamic stresses for severe stenoses of the middle cerebral artery (MCA) M 1 segment.Materials and methodsPatients with severe stenoses of the MCA M1 segment treated with endovascular stent angioplasty were retrospectively enrolled. Three-dimensional digital subtraction angiography before and after stenting was performed; the computational fluid dynamics (CFD) analysis of hemodynamic stresses at the stenosis and normal segments pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…In patients with severe M1 MCA stenosis, Zhang et al reported that successful stenting could reduce the pressure loss across the sICAS lesion compared with that before stenting (means 6.46 Pa vs 12.84 Pa, p<0.001), which could enhance antegrade blood flow. 28 In patients with severe basilar artery stenosis, Zhou et al found significantly reduced WSS (means 14.84 Pa vs 139.49 Pa, p<0.001) at the stenosis segment after stenting treatment. 29…”
Section: Changes Of the Haemodynamic Parameters In Sicas With Stentin...mentioning
confidence: 95%
“…In patients with severe M1 MCA stenosis, Zhang et al reported that successful stenting could reduce the pressure loss across the sICAS lesion compared with that before stenting (means 6.46 Pa vs 12.84 Pa, p<0.001), which could enhance antegrade blood flow. 28 In patients with severe basilar artery stenosis, Zhou et al found significantly reduced WSS (means 14.84 Pa vs 139.49 Pa, p<0.001) at the stenosis segment after stenting treatment. 29…”
Section: Changes Of the Haemodynamic Parameters In Sicas With Stentin...mentioning
confidence: 95%